Instrument for the evaluation of climacteric and menopause in the first level of care - Matzumura-Kasano, Juan P. (2020)
Introduction:The middle-aged female population will increase in the coming years and will require more medical care to relieve climacteric symptoms Objective: To validate an instrument for evaluating climacteric and menopause in primary care Methods: Prospective, cross-sectional, instrument-validation study. The sample was composed of women attending primary care centers. Our research consisted of three stages: initial review (literature review, translation), validation (content validity, pilot study) and psychometric properties (internal consistency and confirmatory factorial analysis). We analyzed the data using SPSS version 20. Results: 136 patients participated, with an average age of 48,6 years ± 5,3 and an average body mass index of 27,8 kg/m2 ± 4,4. In the first stage, we identified the most relevant symptoms: menstrual irregularities, hot flashes, vaginal problems, urinary incontinence, quality of sleep, and mood issues. The instrument was then translated by four professionals. For the second stage, we assessed content validity by expert judgment, obtaining an internal consistency of 0,77 and an initial reliability of 0,79. In the third stage, internal consistency was 0,69 and confirmatory factorial analysis was 0,7. The instrument consists of six questions; obtaining four or more positive answers warrants specialized care. Conclusion: We present a short instrument with adequate content validity and internal consistency, useful for managing climacteric symptoms at the primary care level.